Reconciliation through metissage in higher education - Scott, Bryanna (2021)
As a result of the final report of the Truth and Reconciliation Commission (2015) and its Calls to Action for education, many universities are working to design culturally appropriate curricula and to “Indigenize” their policies. While the intention is to demonstrate reconciliation through institutional practices, rarely do these committees consider the university experiences of Indigenous, let alone Métis students. And rarely do these reconciliation plans veer away from a pan-Indigenous homogenizing approach to Indigenous content, subsuming Métis, and Inuit cultures into First Nations1 as one monolithic category. This Ph.D. study focusses on how Métis peoples’ knowledge, culture, and experience need to be explicitly addressed and discussed as reconciliation in higher education. The study investigates the question: How have university courses and learning experiences impacted Métis peoples’ understanding of their identities, the role of Métis-specific Knowledge, and perspectives on reconciliation in higher education? The research follows a grounded theory approach of constant comparison within a métissage design where Métis storytelling is blended with autobiographical narratives and interview data. Twelve participants, all Métis people living in Ontario and involved in higher education, completed interviews or submitted written responses to semi-structured questions, either as students enrolled in a north-central university, as alumni working in education organizations, or as community members engaged in school systems. The study’s findings demonstrate that a Métis-specific wise-practices approach to including Métis content is mostly absent but greatly needed in higher education curriculum. Through the creation of a métissage-as-reconciliation framework, I argue that Métis perspectives woven into university courses is a critical step towards acknowledging the identities, history, and culture of Métis people while creating more equitable, diverse, and inclusive (EDI) practices for Métis and all students. If Canadian universities want to implement Indigenous initiatives and programs to advance reconciliation, then Métis perspectives must be included for any meaningful engagement, recognition, and retention of Métis learners. Métissage-as-reconciliation offers a curricular framework for representing Métis identity, respectfully including Métis-specific perspectives in course content, and understanding how decolonizing efforts can be attentive to the learning experiences of Métis people. Reconciliation through métissage can ensure a more robust institutional effort to address the TRC’s Calls to Action and support the growing demographic of Métis students in Canadian universities